ASSESSMENT OF SUBSTANCE USE RELATED EXPERIENCE OF MEDICAL STUDENTS IN A PUBLIC MEDICAL UNIVERSITY - Imtiaz, Kashaf; Ammar Ahmad; Muhammad Adnan Rashid; Nighat Haider; Aftab Alam Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Substance use affects all aspects of life of an individual. Males typically have higher tendency. Youth is particularly at risk. Curiosity, peer pressure, lack of knowledge and easy availability are major risk factors. Increasing trends of substance use are seen in medical students despite the fact that they are well aware of adverse effects of addiction. Study of consequences faced by medical students due to substance use is the main aim of research so these effects can be identified early and help can be provided in time. Methods: This was a descriptive cross-sectional study conducted among the students of a public sector Medical University situated in one of the main cities of Pakistan from 15th January to 15th April 2023. A total of 1038 students were recruited to the study using non-probability convenient sampling method. Data were entered & analyzed using SPSS version 26. Results: Only 1.4% (n=15) admitted substance use when direct question was asked and 2.02% (n=21) admitted when asked indirectly. 3.6% (n=38) experienced withdrawal symptoms. Feelings of guilt were observed in 18.5% (n=191), majority of which were first year students (n=51). Families of 3.3% (n=34) were worried due to substance use disorder. 0.3% (n=3) admitted being involved in criminal activity to obtain drugs of abuse. Conclusions: A considerable fraction of medical students were involved in substance use and majority of them faced consequences like medical effects, family issues and being involved in illegal activities.